2023
DOI: 10.1186/s13063-022-07010-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adjunctive treatment with l-carnitine on monitoring laboratory variables in ICU patients: a double-blinded randomized controlled clinical trial

Abstract: Background Critically ill patients must be monitored constantly in intensive care units (ICUs). Among many laboratory variables, nutritional status indicators are a key role in the prognosis of diseases. We investigated the effects of l-carnitine adjunctive therapy on monitoring variables in critical illness. Method A prospective, double-blind, randomized controlled trial was implemented in a medical ICU. Participants were 54 patients, aged > 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A randomized ICU-based clinical trial by Yahyapoor, et al which was published recently, revealed that 3 g LC per day for 7 days in the liquid form via enteral tube feeding in 54 critically ill patients, improved serum Alb and decreased CRP and IL-6 biomarkers in the LC group in comparison to the placebo group which is in line with our results. The major limitation of the mentioned trial was the broadly heterogeneous patients that were included but we focus on septic patients [20,28]. Thirteen clinical trials on the topic of LC supplementation effects on inflammatory biomarkers [21].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized ICU-based clinical trial by Yahyapoor, et al which was published recently, revealed that 3 g LC per day for 7 days in the liquid form via enteral tube feeding in 54 critically ill patients, improved serum Alb and decreased CRP and IL-6 biomarkers in the LC group in comparison to the placebo group which is in line with our results. The major limitation of the mentioned trial was the broadly heterogeneous patients that were included but we focus on septic patients [20,28]. Thirteen clinical trials on the topic of LC supplementation effects on inflammatory biomarkers [21].…”
Section: Discussionmentioning
confidence: 99%
“…41 Creatine, stored in skeletal muscles, undergoes breakdown to fulfill energy requirements in such a population in the condition of deprived energy, and hence, an increased level of both creatine and creatinine 44 is found in AKI patients. Yahyapoor et al, 45 in a double-blinded randomized controlled trial on 54 ICU patients with multiple conditions, observed that providing 3 g L-carnitine supplementation to patients along with feed improved their creatinine levels along with albumin, calcium, alanine transaminase (ALT), and lactate. In our study, the ARDS patients with AKI had elevated creatine levels, indicating higher energy requirements resulting in increased severity, with the results of correlation analysis pointing in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…(Yahyapoor et al, 2023) [137] Randomized controlled trials During major depressive episodes (MDEs), there's a notable decline in the metabolic activity of mitochondria converting l-carnitine to ALC.…”
Section: Double-blinded Randomized Trialmentioning
confidence: 99%